Hepatitis A vaccine immunogenicity 25 years after vaccination in Alaska. Issue 6 (25th August 2020) - Ramaswamy, Maya; Bruden, Dana; Nolen, Leisha D.; Mosites, Emily; Snowball, Mary; Nelson, Noele P.; Bruce, Michael; McMahon, Brian J.
Abstract: The hepatitis A vaccine is recommended for all children greater than or equal to 1 year of age, however, the duration of vaccine protection is unknown and protection through adulthood is crucial to prevent symptomatic hepatitis later in life. We report on 25 years of follow‐up of a cohort of Alaska Native individuals who were vaccinated in early childhood. We assessed the duration of vaccine protection by calculating the geometric mean concentration and proportion of participants with protective levels of IgG antibody to hepatitis A virus (anti‐HAV) (≥20 mIU/mL) every 2 to 3 years. We estimated the amount of time until the anti‐HAV dropped below protective levels using survival analyses. At 25 years, 43 of the original 144 participants were available, mean anti‐HAV levels were 91.5 mIU/mL, and 35 (81.4%) had protective levels of anti‐HAV. Using data from all persons and all time points, a survival analysis estimated 78.7% of participants had protective levels of anti‐HAV at 25 years. The high level of protective antibodies in this cohort indicate that supplemental doses of hepatitis A vaccine are not needed 25 years after completion of the vaccine series. Highlights: Our data indicate that a supplemental vaccine dose is not necessary up to 25 years after hepatitis A vaccine is administered in childhood.